Synergistic Effect between Alcohol Consumption and Familial Susceptibility on Lung Cancer Risk among Chinese Men - Tse, Lap Ah (Public Library of Science, 2012)
We aimed to examine the effect of alcohol consumption on lung cancer risk stratified by smoking, and to explore whether the impact of alcohol was modified by familial susceptibility to cancer. We recruited 1208 male lung cancer incident cases and 1069 community referents during 2004–2006 and collected their lifetime history of alcohol consumption, cigarette smoking, and family cancer history. Unconditional multivariate logistic regression analysis was performed to estimate the adjusted odds ratio (OR). We tested multiplicative-scale interaction between exposures of interest and examined the additive-scale interaction using synergy index. A moderate association between frequent alcohol consumption and lung cancer was observed among men who had family cancer history (OR = 4.22, 95%CI: 2.46–7.23) after adjustment of smoking and other confounders, while the alcohol effect among men without family history was weak (OR = 1.24, 95%CI: 0.95–1.63) and it became no excess in the never smokers. We observed a consistent synergistic effect between alcohol drinking and family cancer history for all lung cancers and the adenocarcinoma, while there was no multiplicative-scale interaction between the exposures of interest (likelihood ratio test for interaction, p>0.05). Our study revealed a possible synergistic effect between alcohol consumption and familial susceptibility for lung cancer risk; however, this observed possible association needs to be confirmed by future larger analytic studies with more never smoking cases.